Analisis Puisi “Tanah Air” Karya Muhammad Yamin Dengan Pendekatan Struktural - Cindy Januarianti; Nur Syifa Qolbiyah Yuningsih (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
Language is an organized communication tool in the form of units, be it words, groups of words, clauses or sentences. Meanwhile, literature is a creative human form that originates from one's thoughts, understanding or even feelings which are expressed in both spoken and written language. Learning Indonesian Language and Literature are two related things. Literary work is a concrete form of language itself. Poetry is one type of fictional literary work. Based on the Big Indonesian Dictionary (KBBI), the notion of poetry or rhymes is a type of literature with a language that is bound by rhythm, rhyme, and the arrangement of stanzas and arrays. The purpose of this research is to analyze the structure of the poem Tanah Air by Muhammad Yamin. The methodology used in this study uses a qualitative descriptive method. The approach used is a structural approach. The data collection technique used is to include the physical structure and mental structure. The result of this article is to find the physical structure and inner structure of Muhammad Yamin's Tanah Air poetry. Included in the physical structure are the form of poetry, diction, concrete words, style of language and imagery. Meanwhile, what is included in the inner structure is the theme, tone, atmosphere, and message.